High PIRCHE Scores May Allow Risk Stratification of Borderline Rejection in Kidney Transplant Recipients - Lezoeva, Ekaterina; Nilsson, Jakob; Wüthrich, Rudolf; Mueller, Thomas F.; Schachtner, Thomas (Frontiers in Immunology, 2022)
Background The diagnosis of borderline rejection (BLR) ranges from mild inflammation to clinically significant TCMR and is associated with an increased risk of allograft dysfunction. Currently, there is no consensus regarding its treatment due in part to a lack of biomarkers to identify cases with increased risk for immune-mediated injury. Methods We identified 60 of 924 kidney transplant recipients (KTRs) with isolated and un-treated BLR. We analyzed the impact of predicted indirectly recognizable HLA epitopes (PIRCHE) score on future rejection, de novo DSA development, and recovery to baseline allograft function. Additionally, we compared the outcomes of different Banff rejection phenotypes. Results Total PIRCHE scores were significantly higher in KTRs with BLR compared to the entire study population (p=0.016). Among KTRs with BLR total PIRCHE scores were significantly higher in KTRs who developed TCMR/ABMR in follow-up biopsies (p=0.029). Notably, the most significant difference was found in PIRCHE scores for the HLA-A locus (p=0.001). PIRCHE scores were not associated with the development of de novo DSA or recovery to baseline allograft function among KTRs with BLR (p>0.05). However, KTRs under cyclosporine-based immunosuppression were more likely to develop de novo DSA (p=0.033) than those with tacrolimus, whereas KTRs with preformed DSA were less likely to recover to baseline allograft function (p=0.023). Conclusions High PIRCHE scores put KTRs with BLR at an increased risk for future TCMR/ABMR and contribute to improved immunological risk stratification. The benefit of anti-rejection treatment, however, needs to be evaluated in future studies.